An exploratory study of power relations in classroom interaction in the government schools of Bangladesh - Haque, Chameli (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2015.